2017
DOI: 10.5812/semj.14532
|View full text |Cite
|
Sign up to set email alerts
|

Patient Absconding and Its Predictors: A 5-Year Retrospective Analysis in a General Teaching Hospital in Tehran, Iran

Abstract: Background and Purpose: Patient absconding from a hospital or leaving without permission is a major challenge with economic and social consequences for patients, healthcare staff, and society. Identification of the characteristics of absconding patients is essential to the prediction and prevention of such behaviors. Methods: This cross sectional study was performed in a large general teaching hospital in Tehran, Iran. Data of 460 absconding patients and 460 nonabsconding patients, admitted during March 2010 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…For instance, the highest rate of absconsion (54.4%) in all the included studies was reported among forensic patients managed in a nonforensic general psychiatric unit in Malawi 42 . Compared to the present study, relatively lower rates of absconsion have been reported in reviews of studies conducted in general psychiatric units, with an average of 12.6%1 (range: 2%-44%), 1 , 58 and the rates in nonpsychiatric general hospitals ranged between 0.27% and 2.4% 59 . While a comparative study on absconsion is currently limited due to the methodological issues outlined earlier (eg, variability in construct, study duration, and contextual factors), it is conceivable that higher rates of absconsion are possible in forensic patients due to unique risk issues described above, especially if they are managed in nonsecure units 42 , 43 .…”
Section: Discussioncontrasting
confidence: 74%
“…For instance, the highest rate of absconsion (54.4%) in all the included studies was reported among forensic patients managed in a nonforensic general psychiatric unit in Malawi 42 . Compared to the present study, relatively lower rates of absconsion have been reported in reviews of studies conducted in general psychiatric units, with an average of 12.6%1 (range: 2%-44%), 1 , 58 and the rates in nonpsychiatric general hospitals ranged between 0.27% and 2.4% 59 . While a comparative study on absconsion is currently limited due to the methodological issues outlined earlier (eg, variability in construct, study duration, and contextual factors), it is conceivable that higher rates of absconsion are possible in forensic patients due to unique risk issues described above, especially if they are managed in nonsecure units 42 , 43 .…”
Section: Discussioncontrasting
confidence: 74%
“…The most important reasons can be due to fatigue and hopelessness, intolerance of hospital, overdose of drugs, addiction, and poisoning, drinking alcoholic drinks, treatment failure, behavioral disorders, unemployment, and receiving unpleasant news [ 5 ]. However, the most important reason for patients to escape from general hospital is the inability to pay the medical costs, which has been mentioned in some studies [ 6 , 7 ]. According to research, absconders are typically young, male, and have been diagnosed with schizophrenia [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most important reasons can be due to fatigue and hopelessness, intolerance of hospital, overdose of drugs, addiction, and poisoning, drinking alcoholic drinks, treatment failure, behavioral disorders, unemployment, and receiving unpleasant news [5]. However, the most important reason for patients to escape from general hospital is the inability to pay the medical costs, which has been mentioned in some studies [6,7]. This behavior can pose many risks, including longer recovering process or uncompleted treatment [8].…”
Section: Introductionmentioning
confidence: 99%